Reliability, Safety and Effectiveness of the Bravo(TM) Capsule: A Catheter-free pH Monitoring System for Evaluation of Gastroesophageal Reflux Disease in Children - Karjoo, Manoochehr (Iranian Association of Gastroerterology and Hepatology, 2012)

(untitled)
BACKGROUND Gastroesophageal reflux disease (GERD) is a common problem seen in pediatrics and adolescents. The Bravo™ pH Monitoring System is a capsule that detects and quantifies the severity of reflux disease. This test is also valuable for evaluation of patients with extra-gastrointestinal manifestations of GERD such as asthma, chronic cough, hoarseness, aspiration pneumonia, and pre/post fundoplication surgery. This study evaluates the safety and reliability of this procedure in children. METHODS From January 2002 to December 2010, 219 patients (85 males and 134 females), ages 6-18 years underwent upper endoscopy with biopsies and placement of the Bravo™ capsule. RESULTS In 201 out of 219 patients, the Bravo™ pH monitoring procedure completed within 48 hours without any complaints. In 3 out of 219 patients, the pH dropped to less than 2 after 30 minutes. This indicated that the capsule moved from the esophagus to the stomach. One other patient deleted all data while playing with the recorder at home. In another patient, there was recorder malfunction. Three patients presented with chest pain, one with chest and back pain and nine patients had a mild sensation of sub-sternal pain for two hours or less. None of the patients needed to retrieve the capsule. CONCLUSION Bravo™ capsule pH monitoring of the esophagus is reliable, safe, well tolerated and free from significant complications, and preferred by young adolescents. With the Bravo™ capsule, adolescents can attend school and continue their normal physical activities without interruption.